Cortico-Muscular Phase Connectivity During an Isometric Knee Extension Task in People With Early Parkinson’s Disease - Nina Omejc; Tomislav Stankovski; Manca Peskar; Milos Kalc; Paolo Manganotti; Klaus Gramann; Saso Dzeroski; Uros Marusic (IEEE Transactions on Neural Systems and Rehabilitation Engineering)
Introduction: Cortico-muscular (CM) interactions provide insights into the flow of information between neural and motor systems. Reduced CM phase connectivity has been linked to functional impairments in clinical populations. Objective: This study aimed to determine whether similar reductions occur in individuals with Parkinson’s disease (PD), characterized primarily by motor impairments. Specifically, it aimed to characterize electroencephalography (EEG) and electromyography (EMG) power spectra during a motor task, assess CM phase connectivity, and explore how an additional cognitive task modulates these measures. Methodology: Fifteen individuals with early-stage PD and sixteen age-matched controls performed an isometric knee extension task, a cognitive task, and a combined dual task, while EEG (128 channels) and EMG (2x32 channels) were recorded. CM phase connectivity was analyzed through phase coherence and phase dynamics modeling. Results: The strongest CM phase coherence was observed in the lower beta band (12.5–15 Hz) over the Cz electrode and was significantly higher in healthy controls compared to individuals with PD during the motor task. The phase dynamics model additionally revealed stronger directional coupling from the Cz electrode to the active muscle, than in the reverse direction, with less pronounced phase coupling in the PD cohort. Notably, CM phase coherence exhibited distinct scalp topography and spectra characteristics compared to the EEG power spectrum, suggesting different mechanisms underlying Parkinsonian pathological beta power increase and CM phase connectivity. Lastly, despite high inter-individual variability, these metrics may prove useful for personalized assessments, particularly in people with heightened CM connectivity.